Seeking the live: Experiencing the COVID-19 pandemic as a postgraduate music student. Issue Volume 21:Number 1(2021)Special Issue:Part 1 (28th August 2021) - Rose, Alice
Abstract : Onaji jikan, onaji kukan. Same time, same place. These are the words I wrote down in an interview this summer—ironically a Zoom interview that took place both at 9 am in Oxford and 5 pm in Osaka. Needless to say, this was not the fieldwork I planned when I began my PhD in 2018, although in some ways it feels fitting for a thesis on digital technologies and the 'live'. Yet today I remain, like many of my peers, so far behind, so 'late', that catching up seems almost impossible. In this article, I reflect on the importance of shared time and place, not only in Japanese 'live culture', but also in my experience of the pandemic as a postgraduate student.